基于VC++的液力机械变矩器特性分析 - 韩庆瑶; 孔志增 (Jixie chuandong)
Combining hydrodynamic transmission and mechanical element, a new hydrodynamic element hydrodynamic mechanical transmission is got. Then the problem that analysis of the new organ comes out. A software to get the hydrodynamic transmission’s parameters from database is designed and the new element’s parameters and characteristic chart is given using VC++ and Access database.